EMPOWERING TEACHERS: SOME INSIGHTS ON IMPROVING TEACHER EFFICACY - Panchamukhi, Pushkarni (IJRDO- Journal of Educational Research, 2022)
The focus of policy makers in India is gradually shifting from improving access to improving the quality of education. There is little debate in literature on the significance and instrumental role of teachers in achieving educational outcomes, improving test score of students or raising their overall wellbeing. However, there is much debate on how to evaluate their effectiveness and what are the various factors that determine their effectiveness. The objective of this paper is to specifically investigate the various factors that determine the efficacy of teachers in improving the quality of education. After classifying these factors into three broad categories termed as systemic factors, school-specific factors and individual specific factors, we bring in the concept of cultural capital given by Bourdieu and apply it specifically for teachers. Parallel to Bourdieu’s idea of social reproduction, we introduce the term ‘edification reproduction’ to explain how beliefs, perceptions and practices about teaching get transmitted across generations creating a divide in the society. Finally, we discuss some of the proposals for teachers made by the National Education Policy, 2020 and connect with how they address the self-efficacy perceptions among teachers in India. We conclude with remarks on how early training for teacher could help develop self-efficacy among teachers.